Keynes: The Recent Return of the Master - Robert Skidelsky (Wirtschaftsdienst)
Abstract The current crisis repeats the patterns of previous crises. Against a backdrop of falling production and rising unemployment, central banks and governments around the world are trying to save their economies from a major crash. The formula for this stabilisation policy is based on the lessons of the British economist John Maynard Keynes, which he described after the Great Depression in 1936 in his “General Theory of Employment, Interest, and Money”. For the slump but also beyond, Keynes provided insightful policy recommendations that can be applied in the 21st century.